2020
DOI: 10.1111/all.14563
|View full text |Cite
|
Sign up to set email alerts
|

RAGE and TLR4 differentially regulate airway hyperresponsiveness: Implications for COPD

Abstract: Background The receptor for advanced glycation end products (RAGE) and Toll‐like receptor 4 (TLR4) is implicated in COPD. Although these receptors share common ligands and signalling pathways, it is not known whether they act in concert to drive pathological processes in COPD. We examined the impact of RAGE and/or TLR4 gene deficiency in a mouse model of COPD and also determined whether expression of these receptors correlates with airway neutrophilia and airway hyperresponsiveness (AHR) in COPD patients. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Taken together, this provides reasonable explanation that RAGE plays an exacerbating role in the pathogenesis of cognitive disorder in diabetes, as microglia activation and neuronal damage occur almost simultaneously. These ndings are consistent with the evidence that transmembrane receptors may directly interaction with various protein in different cells to induce diverse disease processes [39]. It is worth noting that study focusing on the accurate domain by which RIPK1 interaction with RAGE requires future clari cation.…”
Section: Discussionsupporting
confidence: 87%
“…Taken together, this provides reasonable explanation that RAGE plays an exacerbating role in the pathogenesis of cognitive disorder in diabetes, as microglia activation and neuronal damage occur almost simultaneously. These ndings are consistent with the evidence that transmembrane receptors may directly interaction with various protein in different cells to induce diverse disease processes [39]. It is worth noting that study focusing on the accurate domain by which RIPK1 interaction with RAGE requires future clari cation.…”
Section: Discussionsupporting
confidence: 87%
“…However, Allam et al demonstrated that RAGE and TLR4 differentially regulate airway responsiveness to cigarette smoke (CS). Indeed, the authors used RAGE and TLR4 knockout mice and found that only RAGE deletion procured protection against CS-induced neutrophils and airway responsiveness [ 43 ]. In our amniotic context, we tested at the beginning of the project the impact of CSC on TLR4 expression and found that there is no induction (ratio 1.1 by qRT-PCR, Supplementary Data S1, See Supplementary Files ) excluding the TLR4 hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of PRRs via PAMPs/DAMPs is a critical component of the innate immune response to damage, causing activation of numerous proinflammatory pathways involved in the immune response to pathogens as well as contributing to disease pathogenesis of non-infectious lung diseases. For example, TLR4 and the receptor for advanced glycation end-products (RAGE) are widely expressed throughout the respiratory epithelium, where they have pivotal roles in triggering the proinflammatory response [22,23].…”
Section: Sensing Danger: Pamp and Damp Signallingmentioning
confidence: 99%